(untitled) (International Journal of Food and Nutritional Sciences, 2022)
India implemented GST on July 1st, 2017. Value added tax (VAT), excise, sales, and other indirect taxes are only a few of the ones that are integrated in the GST, also known as one nation, one tax. GST implementation results in a reform of the tax code. GST has a variety of effects on durable consumer products. Most consumer durable products had a little higher GST tax when the GST was first adopted, but many of these goods had their GST slab rates decreased from 28% to 18%, and these changes in GST rates had an effect on consumer durable goods. The major goal of the study is to assess how consumers’ perspectives have changed in terms of their satisfaction with the effects of the GST on consumer durables in Trivandrum.